Cutaneous Manifestations in Patients with Covid-19 in the Practice of Emergency Medical Care - N. F. Plavunov; V. A. Kadyshev; A. M. Sidorov; L. N. Proskurina; N. A. Goncharova (SINAPS LLC, 2020)
Currently, information about the epidemiology, clinical features, prevention and treatment of coronavirus infection affected by SARS-CoV-2 (COVID-19) is constantly updated and updated. The most common clinical manifestations of COVID-19 are fever, symptoms of intoxication, cough, shortness of breath, fatigue, chest congestion, decreased sense of smell and taste, less often - abdominal pain, vomiting, diarrhea, and others. For the current period, there are data from clinical observations describing skin lesions in the new COVID-19 coronavirus infection. One of the first descriptions of skin manifestations in COVID-19 was published by the Italian dermatologist Recalcati S. (2020), who provided data on possible types of skin lesions as a variant of the manifestation of a new COVID-19 coronavirus infection.This paper presents the confirmed cases COVID-19 infection with skin lesions, from the practice of specialists of mobile teams of emergency medical care state budgetary institution «Station of emergency medical care to them. A.S. Puchkov» in Moscow, at survey of the patients at disease onset. In the initial period of the disease, when examining patients, various morphological elements were observed: papulo-vesicular, papulo-squamous, erythematous, urticary, and others, their localization was also different. Whether the described changes on the skin are associated with direct exposure to the pathogen COVID-19 or are a manifestation of secondary pathogenetic factors (infectious-allergic, allergic, toxic, etc.) is not currently known. Further accumulation of clinical observations of skin manifestations in this disease is necessary in order to analyze and evaluate their diagnostic and prognostic value.